PERAN MEKANISME GOOD CORPORATE GOVERNANCE DALAM MENINGKATKAN REPUTASI PERUSAHAAN SERTA DAMPAKNYA TERHADAP KINERJA KEUANGAN - Jao, Robert; Tangke, Paulus; Holly, Anthony; Loandy, Bill Kreshna (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2022)
This research is aimed to investigate the role of good corporate governance as a mechanism to improve corporate reputation as a mediating effect influence on financial perfomance. This research uses secondary data obtained by using observation method. The data source in this research is the annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 to 2019. The sample were selected using purposive sampling method, with a total of 43 companies. Method used in this research uses path analysis. The result of this research indicate that independent commissioner and commissioner board meeting has a positive and significant effect on corporate reputation. However, institutional ownership has a positive but insignificant effect on corporate reputation. Independent commissioner, commissioner board meeting, and insititutional ownership has a positive but insignificant effect on financial performance. Corporate reputation has a positive and significant effect on financial performance. The sobel test result indicate that corporate reputation mediates the effect of independent commissioner and commissioner board meeting on financial performance and belong to full mediation type. Corporate reputation does not mediate the effect of intitutional ownership on financial performance.